Triplex-forming oligonucleotides: a third strand for DNA nanotechnology. Issue 3 (8th December 2017) - Chandrasekaran, Arun Richard; Rusling, David A
Abstract: DNA self-assembly has proved to be a useful bottom-up strategy for the construction of user-defined nanoscale objects, lattices and devices. The design of these structures has largely relied on exploiting simple base pairing rules and the formation of double-helical domains as secondary structural elements. However, other helical forms involving specific non-canonical base-base interactions have introduced a novel paradigm into the process of engineering with DNA. The most notable of these is a three-stranded complex generated by the binding of a third strand within the duplex major groove, generating a triple-helical ('triplex') structure. The sequence, structural and assembly requirements that differentiate triplexes from their duplex counterparts has allowed the design of nanostructures for both dynamic and/or structural purposes, as well as a means to target non-nucleic acid components to precise locations within a nanostructure scaffold. Here, we review the properties of triplexes that have proved useful in the engineering of DNA nanostructures, with an emphasis on applications that hitherto have not been possible by duplex formation alone.